Fusions near telomeres occur very early in the amplification of CAD genes in Syrian hamster cells. - Smith, K A (1992)
Previous analyses by fluorescence in situ hybridization of structures present 20-30 cell generations after the primary events of mammalian gene amplification have shown that tens of megabases of DNA separate each copy of the selected gene in chromosomal arrays that contain up to 15 copies. Since these structures are very unstable, it is necessary to study amplified DNA as soon as possible after it has been formed to relate the structures observed to the primary mechanisms that generated them. Previously, new amplifications of the CAD gene were analyzed in colonies of 10(5) N-(phosphonoacetyl)-L-aspartate-resistant Syrian hamster BHK cells. CAD is on the p arm of chromosome B9 and the amplified genes were usually found in large extensions of B9p, with one copy in its normal position. We now report that dividing drug-resistant cells have been physically separated from static drug-sensitive cells, to allow the amplified structures to be observed only a few cell generations after they have been formed. The most informative results are that about one-third of the newly formed chromosomes carrying amplified CAD genes are dicentric and that about half of these carry two B9q arms. These observations reveal that recombination between the p telomeric regions of two B9 sister chromatids is an important primary event of amplification in this system. The resulting dicentric chromosomes can then enter bridge-breakage-fusion cycles that provide the means to increase the number of CAD genes per cell in successive generations by an asymmetric distribution at each cell division.